Absorption of bioactive peptides following collagen hydrolysate intake: a randomized, double-blind crossover study in healthy individuals - Virgilio, Nicolina; Schön, Christiane; Mödinger, Yvonne; van der Steen, Bastiaan; Vleminckx, Sara; van Holthoon, Frédérique L.; Kleinnijenhuis, Anne J.; Silva, Catarina I. F.; Prawitt, Janne (Frontiers in Nutrition, 2024)
Background: Collagen hydrolysates (CH) in functional foods and supplements are dietary sources of amino acids (AAs) and di-and tripeptides linked to various health benefits. This study aimed to investigate the single-dose bioavailability of skin- and hide-derived CH from fish, porcine and bovine origin with different molecular weights (bovine 2000 Da and 5000 Da). Methods: A randomized, double-blind crossover clinical study was performed with healthy volunteers assessing the plasma concentration of free and peptide-bound hydroxyproline (Hyp) as well as selected peptides reported to be abundantly present in collagen. Results: The pharmacokinetic endpoints demonstrated comparable uptake of free Hyp from all CH. A higher amount of total compared to free Hyp indicated the uptake of substantial amounts of Hyp-containing di- or tripeptides. Conclusion: Independently of source and molecular weight, all CH yielded relevant plasma concentrations of the investigated metabolites. Larger studies are needed to estimate an ideal level of selected circulating metabolites needed to trigger distinct physiological reactions in target tissues.